2015
DOI: 10.1186/s12915-015-0188-3
|View full text |Cite
|
Sign up to set email alerts
|

A herbivore-induced plant volatile interferes with host plant and mate location in moths through suppression of olfactory signalling pathways

Abstract: BackgroundPlants under herbivore attack release volatiles that attract natural enemies, and herbivores in turn avoid such plants. Whilst herbivore-induced plant volatile blends appeared to reduce the attractiveness of host plants to herbivores, the volatiles that are key in this process and particularly the way in which deterrence is coded in the olfactory system are largely unknown. Here we demonstrate that herbivore-induced cotton volatiles suppress orientation of the moth Spodoptera littoralis to host plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 69 publications
0
78
0
Order By: Relevance
“…Yet it remains unclear why male and female leafroller moths would be attracted to these binary blends of a benzenoid volatile and acetic acid. Previous studies with plant‐feeding Lepidoptera (primarily noctuids and pyralids) have correlated the presence of larval feeding on a host plant with the repulsion of the conspecific adults . However, this response has not always occurred in field studies .…”
Section: Discussionmentioning
confidence: 99%
“…Yet it remains unclear why male and female leafroller moths would be attracted to these binary blends of a benzenoid volatile and acetic acid. Previous studies with plant‐feeding Lepidoptera (primarily noctuids and pyralids) have correlated the presence of larval feeding on a host plant with the repulsion of the conspecific adults . However, this response has not always occurred in field studies .…”
Section: Discussionmentioning
confidence: 99%
“…(E)-DMNT inhibits male attraction towards the sex pheromone (Hatano et al 2015) and is part of a volatile blend that is responsible for the avoidance of herbivore-induced cotton plants by ovipositing females (Zakir et al 2013b). The investigation of its neural representation in the antennal lobe evidenced that (E)-DMNT inhibits overall antennal lobe activation by the sex pheromone and by an attractive synthetic blend mimicking host plant odor (Hatano et al 2015). Whether this pattern reflects the neural mechanism responsible for avoidance of unsuitable plants by S. littoralis can only be confirmed by replicating the experiment with other behavioural antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the ecological aspects, studies on the olfactory basis of host plant perception and attraction in S. littoralis have, to date, mostly focused on a single model host plant: cotton Hatano et al 2015;Kromann et al 2015;Saveer et al 2012). Indeed, GC-EAD active plant volatiles have only been described for cotton plus two non-hosts with a negative impact on S. littoralis reproductive behaviour: a toxic plant and a gymnosperm (Binyameen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have identified natural odorants that interfere with responses to sex pheromones, at the molecular, neurophysiological, and behavioral levels. For instance, (E)-4,8-dimethyl-1,3,7-nonatriene (DMNT), a herbivore-induced plant volatile, interferes with the detection of both sex pheromone and host-derived attractants in the Egyptian cotton leaf worm, Spodoptera littoralis (Lepidoptera), reducing attraction to both sex pheromones and host attractants (Hatano et al, 2015). Because DMNT also attracts natural enemies of herbivores it might be a good target for sustainable agricultural pest control.…”
Section: Targeting Species-specific Receptors Should Be Desirable Fromentioning
confidence: 99%